Pacific seasonal workers: Learning from the contrasting temporary migration outcomes in Australian and New Zealand horticulture. Issue 3 (22nd September 2018) - Curtain, Richard; Dornan, Matthew; Howes, Stephen; Sherrell, Henry
Abstract: "Crowding out" is a widely accepted claim in migration analysis, which posits that the preference of profit‐maximising employers for irregular and minimally regulated migrants overregulated alternatives will undermine, if not condemn to failure, well‐regulated temporary migration schemes. In this paper, we test the crowding out hypothesis by examining the experience with well‐regulated seasonal migrant worker programs in the horticultural sectors of Australia and New Zealand. This experience, which in both countries has involved recruitment of workers from the Pacific Islands, has been divergent, despite the two programs being similar in design. Our findings suggest that the relative attractiveness of regulated and unregulated migrant labour sources depends on a range of factors, including the export orientation of the sector, the costs of collective action and regulation, differences in policy design and implementation, and external factors. Depending on industry and economy‐wide characteristics, quality and reputational benefits for employers can offset the cost of regulation.